Healing the heart - U Tun Aung, Maularna Akbar Shah (2019)
Beware, in the body there is a piece of flesh; if it is sound, the whole body is sound and if it is corrupt the whole body is corrupt, and hearken it is the heart.” [Muslim] The heart is an important organ in the human body and it’s functionality is vital for the human body, Muslim believe that the heart could be the place of good and evil, a sound heart will keep it’s body sound and an evil heart will corrupt the body. This is because Allah has made the heart the center of all feelings and emotions and it is through the heart that a person’s personality and everything else in their life is comprehended. Quran mentions the heart in numerous places because the spiritual nourishment of the heart comes from the Quran and by getting closer to Allah. Join our speaker as he discusses the diseases of the heart and ways that keep our spiritual heart free from it.